Ukucela ingqula (We ask that our voice be heard) (International Library of African Music, 2015)
Ukucel' ingqula is a song for umngqungqo, the women's dance at girl's initiation. As is usual in Xhosa traditional songs, many of the words are exclamations. The pertinent texts are the title: Ukucela ingqula, "to ask that our voice be heard,” i.e. please listen to us; Hohoyo … zintombi he: (it is) the girls… Similar texts are sung several times. The lyrics tell us that a girl needs to be initiated, and speaks to her father.
Keywords: African Music